Ratemaking as Climate Adaptation Governance - Monast, Jonas J. (Frontiers in Climate, 2021)
Electric utilities are directly affected by, and in some cases are a source of, many pressing climate adaptation challenges: wildfires, vulnerable infrastructure, extreme storms, and drought. The state Public Utilities Commission (PUC) is one of the most consequential government agencies guiding the electricity sector’s response to climate change. Rate-regulated utilities may not charge ratepayers for new capital investments without PUC approval. When PUCs decide which costs are eligible for rate recovery, they also define which risks utilities seek to manage and which hedging strategies they use to do so. This Article argues that the foundational principles of ratemaking allow the state PUC to manage many aspects of electricity sector adaptation planning, coordination, and implementation. The Article begins with an overview of ratemaking for electric utilities and identifies how the process is an exercise in risk management. The Article then explains how a risk governance perspective can position the PUC to explicitly incorporate climate adaptation into ratemaking procedures as well as help coordinate adaptation policy across multiple agencies.